SOSIALISASI PERSONAL HYGIENE MELALUI VISUAL KONTEN KEPADA MASYARAKAT KELURAHAN PESAWAHAN SEBAGAI LANGKAH PENINGKATAN DERAJAT KESEHATAN - Setiajaya, Arif; Hasiany, Sillak; Awan, Fajriharish Nur; Prasetio, Bambang; Alifa, Nabilla Putryandri (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Personal hygiene (PHy) is a public health effort that studies environmental conditions on human health, efforts to prevent disease from occurring due to the influence of the health environment, and create environmental conditions in such a way that health care is guaranteed. The Peswahan Village community has not implemented PHy because of a lack of self-awareness, the sources of information and education provided, and a decline in health status. Socialization through visual content is carried out with the aim that village communities can understand the importance of PHy and in the end can change bad behavior to be good in a sustainable manner. Socialization efforts are carried out by holding meetings and counseling for the local community. The results of this socialization show an increase in public awareness about the importance of PHy. Based on the pre-test and post-test data, it shows a very significant change in public knowledge in answering questions related to personal hygiene correctly, increasing from 38.35% to 61.65%.